Analysis of Competitive Marketing and Financial Strategies in the Development of the Marketing Mix - Mandung, Fitriani; Amra, Wahida (Manunggal Halim Jaya, 2025)
This research aims to determine and analyze the influence of Competitive Marketing and Financial Strategies on the Development of the Marketing Mix among Weekly Traders at Car Free Day Boulevard, Makassar City. This study uses a quantitative research approach. The research was conducted through a survey method, employing questionnaires as the main data collection instrument. The data obtained were then processed using SPSS version 23 to analyze and determine the research results. The sample consisted of 138 respondents, selected from a total population of 212 weekly traders at Car Free Day Boulevard, Makassar City, who met the criteria of using tents during trade. The sample size was determined using the Slovin formula with a margin of error of 0.05. The analytical methods employed in this research included Descriptive Analysis, Validity and Reliability Tests, Classical Assumption Tests (Normality, Multicollinearity, and Heteroscedasticity), as well as Multiple Linear Regression Analysis, all of which were aligned with the conceptual framework developed in the study. The results of the study indicate that Competitive Marketing and Financial Strategies have a positive and significant effect on the development of the marketing mix among weekly traders at Car Free Day Boulevard, Makassar City.